A Sparse Mixture-of-Experts Model With Screening of Genetic Associations to Guide Disease Subtyping - Courbariaux, Marie; De Santiago, Kylliann; Dalmasso, Cyril; Danjou, Fabrice; Bekadar, Samir; Corvol, Jean-Christophe; Martinez, Maria; Szafranski, Marie; Ambroise, Christophe (Frontiers in Genetics, 2022)
Identifying new genetic associations in non-Mendelian complex diseases is an increasingly difficult challenge. Yet, these diseases seem to have a significant part of heritability to explain. This missing heritability could be explained by the existence of subtypes involving different genetic factors. Taking genetic information into account in clinical trials can therefore be of interest to guide the process of subtyping a complex disease. Most methods dealing with multiple sources of information rely on data transformation, with two main tendencies regarding disease subtyping in that situation: i) the clustering of clinical data followed with posterior genetic analysis and ii) the clustering of clinical and genetic variables. Both face limitations that we propose to leverage. This work proposes an original method for disease subtyping from both longitudinal clinical variables and high-dimensional genetic markers via a sparse mixture of regressions model. The added value of our approach lies in its interpretability regarding two aspects. First, our model links both clinical and genetic data with regard to their respective initial nature (i.e. without transformation) and does not need post-processing to come back to the original information to interpret the subtypes. Also, it can address large-scale problems thanks to a variable selection step to discard genetic variables that may not be relevant for subtyping. The proposed method is validated on simulations. A dataset from a cohort of Parkinson's disease patients was also analyzed. Several subtypes of the disease as well as genetic variants having potentially a role in this typology have been identified.